DEVELOPMENT STRATEGY FOR MAK’AIF ANA AND PAOS’KENAT PATTERN IKAT WEAVING IN OENENU UTARA VILLAGE, BIKOMI TENGAH DISTRICT, NORTH CENTRAL TIMOR REGENCY - Katharina Ignosa Talan; Yuliati Sengkoen; Natalia Lily Babulu (Jurnal Manajemen Bisnis Dan Organisasi, 2026)
The main problem in this study is that the artisans of Mak’aif Ana and Paos’kenat patterned ikat weaving in Oenenu Utara Village have different production quantities and incomes, caused by different business development strategies. This study aims to identify the development strategies for Mak’aif Ana and Paos’kenat patterned ikat weaving in Oenenu Utara Village, Bikomi Tengah District. This research was conducted in Oenenu Utara Village, Bikomi Tengah District, North Central Timor Regency. The population was 145 people, and the sample consisted of 67 people. Data sources came from primary and secondary data. Data collection methods used observation, interviews, and questionnaires. The data analysis technique used is SWOT analysis. The research results show that the weavers of Motif mak’aif ana and paos’ kenaf ikat fabrics have IFAS values (strengths of 3.260 and weaknesses of 3.190) and EFAS values (opportunities of 3.313 and threats of 3.077). The SWOT analysis using a Cartesian diagram shows that the weavers of Motif mak’aif ana and paos’ kenaf ikat fabrics are in Quadrant I (Positive-Positive). This position indicates that the weavers of Motif mak’aif ana and paos’ kenaf ikat fabrics are strong and have opportunities. The recommended strategy is progressive, meaning that the weavers of Motif mak’aif ana and paos’ kenaf ikat fabrics are in prime and stable condition, making it very possible to continue expanding, increase growth, and achieve maximum progress.